ANALISA IMPLEMENTASI DISIPLIN KERJA DAN MOTIVASI KERJA BERBASIS ABSENSI ONLINE JATHILAN TERHADAP PENINGKATAN PRODUKTIVITAS PERTANIAN DI KABUPATEN PONOROGO - Yulvida Putri Andini; Supriyono Supriyono; Sumarji Sumarji (Universitas Islam Kadiri, 2020)
The purpose of this researchare:[1] to determine the positive and significant influence of work discipline and work motivation on increasing agricultural productivity in Ponorogo Regency. The research method used multiple linear regression analysis. Multiple linear regression analysis is used to determine cause and effect by determining the Work Productivity of Agriculture Ponorogo of ASN as the dependent variable (Y), Work Discipline (X1) and Work Motivation (X2) as the Independent variable. The results obtained after conducting the study are: 1) Based on the results of the Work Discipline variable analysis of ASN work productivity has a positive and significant effect, This is based on the results of data analysis using SPSS 16 showing the value of t-count is greater than ttable (t-count = 2.224, t-table = 1.667 ) which means that work discipline is able to have a positive and significant effect on increasing the productivity of work in ASN Ponorogo Regency; 2) Based on the results of the analysis of the variable Work Motivation on employee productivity has a positive and significant effect. This is based on the results of data analysis using SPSS 16 showing t-count greater than t-table (tcount = 2.718, t-table = 1.667) which means work motivation is able to have a positive effectand significant to the increase in work productivity of ASN Ponorogo Regency. 3) The test results show that F-count19.525> F-table 3.12 which means that jointly Work Discipline and Work Motivation has a significant positive effect on the work productivity of the Department of Agriculture's employees in Ponorogo Regency. As a result of an increase in ASN work productivity, indirectly, the productivity rate of the agribusiness sector has increased, especially in rice and horticulture production, each experiencing an increase of 6.67% for riceand 55% for horticulture. Keywords: Work discipline, Work Motivation, Productivity